Effects of bacterial lipopolysaccharide and Shiga Toxin on induced Pluripotent Stem Cell-derived Mesenchymal Stem Cells - Martire Greco, Daiana (2023)
Background: Mesenchymal stem cells (MSCs) can be activated by different bacterial toxins. Lipopolysaccharides and Shiga Toxin (Stx) are the main toxins necessary for hemolytic uremic syndrome development. The main etiological event in this disease is endothelial damage that causes glomerular destruction. Considering the repairing properties of MSC, we aimed to study the response of MSC derived from induced pluripotent stem cells (iPSC-MSC) to LPS and/or Stx and its effect on the restoration of injured endothelial cells. Methods: iPSC-MSC were treated with LPS and or/Stx for 24 h and secretion of cytokines, adhesion, and migration were measured in response to these toxins. In addition, conditioned media from treated iPSC-MSC were collected and used for proteomics analysis and evaluation of endothelial cell healing and tubulogenesis using human microvascular endothelial cells 1 as a source of endothelial cells. Results: The results obtained showed that LPS induced a proinflammatory profile on iPSC-MSC, whereas Stx effects were less evident, even though cells expressed the Gb3 receptor. Moreover, LPS induced on iPSC-MSC an increment in migration and adhesion to a gelatin substrate. Addition of conditioned media of iPSC-MSC treated with LPS + Stx, decreased the capacity of human microvascular endothelial cells 1 to close a wound, and did not favor tubulogenesis. Proteomic analysis of iPSC-MSC treated with LPS and/or Stx revealed specific protein secretion patterns that support the functional results described. Conclusions: iPSC-MSC activated by LPS acquired a proinflammatory profile that induces migration and adhesion to extracellular matrix proteins but the addition of Stx did not activate any repair program to ameliorate endothelial damage, indicating that the use of iPSC-MSC to regenerate endothelial injury caused by LPS and/or Stx in hemolytic uremic syndrome could not be the best option to consider to regenerate a tissue injury.